Vote Trading and Electoral Success in Nigerian Democracy - Mayowa, Ilori Oladapo (International Journal of Criminology and Sociology, 2021)
Democracy is based on the principle of the majority able to choose who leads them in a free and fair context devoid of external interference and political influence. The right to elect a wrong candidate is even part of democracy. The law cannot regulate the legitimate choices that the democratic free will is entitled to make. It chooses what it will. It rejects what it will not choose, or else the democratic free will ceases to be what it fundamentally ought to be, namely “free”. Vote trading is a concept in the Nigerian democratic experience. The issue of vote-trading has been in Nigeria's democracy since its inception but became prominent during the present democratic dispensation. Vote buying has been serving as a clog in the wheel of free choice which is the hallmark of a democracy. Unfortunately, not all people that being influenced by vote-buying know what is going on. Some people indulge in the act of vote-trading unknowing. This study which is mainly based on literature and conceptually looked at the influence of vote trading on voter’s free choice, the factors that influenced both vote buying and selling, and how it can be curbed. Consequently, past literature, like journals, books, and other publications on vote-trading were considered in this study.